Quantum Dots in Graphene Nanoribbons - Wang, Shiyong; Kharche, Neerav; Girao, Eduardo Costa; Feng, Xinliang; Muellen, Klaus; Meunier, Vincent; Fasel, Roman; Ruffieux, Pascal (Nano Letters, 2017)
Graphene quantum dots (GQDs) hold great promise for applications in electronics, optoelectronics, and bioelectronics, but the fabrication of widely tunable GQDs has remained elusive. Here, we report the fabrication of atomically precise GQDs consisting of low-bandgap N = 14 armchair graphene nanoribbon (AGNR) segments that are achieved through edge fusion of N = 7 AGNRs. The so-formed intraribbon GQDs reveal deterministically defined, atomically sharp interfaces between wide and narrow AGNR segments and host a pair of low-lying interface states. Scanning tunneling microscopy/spectroscopy measurements complemented by extensive simulations reveal that their energy splitting depends exponentially on the length of the central narrow bandgap segment. This allows tuning of the fundamental gap of the GQDs over 1 order of magnitude within a few nanometers length range. These results are expected to pave the way for the development of widely tunable intraribbon GQD-based devices.
CRIS-Team Scopus Importer:2023-03-20
Keywords: density functional theory; graphene nanoribbon; Graphene quantum dot; scanning tunneling spectroscopy; screening